2013
DOI: 10.1002/adma.201302021
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Porous Low‐k Dielectric Films Based on a New Structural Amorphous Fluoropolymer

Abstract: A non-porous and amorphous fluoropolymer PFN with low dielectric constant of 2.33 and dielectric loss less than 1.2 × 10(-3) is reported here. PFN also exhibits good mechanical properties and high thermostability. This study is a new example of a fully dense material showing a low k value and having good thermo/mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 30 publications
4
144
0
Order By: Relevance
“…21,22 Furthermore, the existence of uorinate and stiff non-polar structure can also decrease moisture absorption and improve the thermal stability of materials. 23 Sasaki 24 reported that the bisphenol A type epoxy resin cured with uorinated phthalic anhydride had the lowest dielectric constant (2.77) and dielectric loss factor (0.01) among all cured epoxy resins.…”
Section: -9mentioning
confidence: 99%
“…21,22 Furthermore, the existence of uorinate and stiff non-polar structure can also decrease moisture absorption and improve the thermal stability of materials. 23 Sasaki 24 reported that the bisphenol A type epoxy resin cured with uorinated phthalic anhydride had the lowest dielectric constant (2.77) and dielectric loss factor (0.01) among all cured epoxy resins.…”
Section: -9mentioning
confidence: 99%
“…The dielectric constants of the cured fluorinated benzoxazines P1 and P2 were measured by the capacitance method at various frequencies, which has high-accuracy measurements. 52 The parallel plate capacitors were fabricated on goldcoated glass slides by spin-coating a solution of the appropriate monomer in THF. The resulting slides were cured via the optimized curing profiles.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In the last few decades, various low k materials [1][2][3][4][5][6][7][8][9] including silicates, polyimides, benzoxazine, SiLK, or benzocyclobutene have been developed, whereas commercially available low k materials with low cost are rare. The application of new low dielectric constant polymers will enable the development of future generations of lower cost and higher performance integrated circuits (ICs).…”
Section: Introductionmentioning
confidence: 99%